Level Changes of Traffic Noise in Kerman City, Southeast Iran - M Malakootian; M Ahmadian; K Yaghmaeian; Sh Dowlatshahi; MR Ghotbi Ravandi (Tehran University of Medical Sciences, 2012)
Background: The purpose of this research was to determine the traffic noise level and changes in the Kerman City, southeast Iran in recent years. Methods: This cross-sectional study was carried out in 2008 to investigate the existing noise situation in Kerman. Sound levels (LMax, LMin, Leq, L99, L90, L50 and L10) were determined throughout 13 stations using sound level measurement system (model, CEL-440). Number of passing vehicles was also assessed at the sampled stations. Results: Sound level in all sampled stations was higher than Iran and World Health Organization guidelines. Comparison of Leq in different hours using statistical tests showed significant difference between different hours with 95 % confidence coefficient (P=0.01). Comparison of Leq throughout the week also showed that there was a significant difference (P=0.001) between Friday and workday. The comparison of Leq with the number of passing vehicles using Pearson correlation statistical test showed significant difference between the number of heavy vehicles passed and the level of Leq (P=0.001). It also showed that number of heavy vehicles caused the most noise levels. Conclusion: The results of this study compared to a similar study conducted in 1999 showed an increasingly high noise level. Noise level increased from 1999 to 2008 by 3.89 % which is indicative of an increase in noise emission sources.